(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Salinity is one among most serious ecological issues affecting farmed vegetation yield although most seeds are prone to saline induced by excessive salt content in soil, & amount of l& affected by it is increasing by day.. Average yields for all main crops are a fraction of record yields, ranging between 20% & 50%; se losses are majorly owing to dearth & excessive soil salinity, climatic circumstances that are expected to worsen in many locations as a result of global climate change. number of variations & mitigation techniques are m&atory for deal with such consequences. In order to generate better breeds, salinity stress can be reduced by effective resource management & crop/livestock growth. However, because such treatments are time-consuming & expensive, simple & low-cost biological options for salinity stress reduction that can be adopted rapidly are needed.. Microorganisms with unique characteristics like salt tolerance, genetic diversity, synsis of suitable solutes, & generation of vegetation growth boosting hormones, bio-control capability, & contact with crop vegetations may play a major role in this regard.